Strategi Pengembangan Paket Oleh-Oleh Olahan Salak di Kelompok Tani Ambudi Makmur 2 - Sayekti, Ayutyas; Amaliyah, Rizqiyatul (Institut Pertanian Bogor, 2023)
Ambudi Makmur 2 Farmer Group is an agribusiness company in Bangkalan Regency whose main commodity is engaged in salak crops. Agribusiness activities in this company include on-farm activities and salak processing activities. The COVID-19 pandemic caused sales of processed salak products to decline and this condition had an impact on decreasing company revenue. This study aims to formulate a strategy to increase sales of processed salak products in the new normal period through sales in the form of processed salak souvenir packages. The target market for salak processed souvenir packages is not only Bangkalan tourists but also the general public around Bangkalan. The methods used are SWOT analysis, non-financial analysis, and financial analysis with respondents being business voters, employees, consumers and tourism officials. The strategy used by the Ambudi Makmur 2 Farmer Group for planning business development ideas in the new normal period is the S-T (Strength-Threats) strategy by developing souvenir packages processed by salak. Based on the results of non-financial analysis and financial analysis, the development of this salak processed souvenir package is feasible to run.